Ultrasonic Investigation of Ternary Mixtures of Crotonaldehyde at 298.15, 303.15 and 308.15 K - Senthamil Selvi, C.; Venkataramanan, K.; Kannappan, V.; Thenmozhi, C.; Ravich, S. (Asian Journal of Chemistry, 2014)
Densities, absolute viscosities and ultrasonic velocities of ternary mixtures of crotonaldehyde and acetone in hexane have been measured for the ternary mixtures at 298.15, 303.15 and 308.15 K in different concentrations under atmospheric pressure. These properties have been used to calculate various thermo-chemical parameters. The variations in these parameters have been studied in terms of nature and extent of interaction. By using the ultrasonic velocity (U), density (r) and coefficient of viscosity (h), other acoustical parameters were calculated. The non-linearity in the variation of viscosity is explained in terms of hydrogen bond formation between components of mixtures. The variation in ultrasonic velocity depends on the intermolecular free length on mixing. The value of intermolecular free length increases with increase in temperature and it is maximum at 308.15 K. It shows that weak interaction takes place at higher temperature. The results have been interpreted in terms of specific intermolecular interactions present in the mixtures and are found to support each other.